Geo‐sociocultural influences on empathy. Issue 7 (3rd May 2019) - Kelly, James; Easton, Graham
Abstract : Kelly and Easton reflect upon Ponnamperuma et al.'s investigation of the potential for regional variation in reports of empathy change during medical training.